I need to solve for ALL values of x:

(5(x-4)/6) + ((x+4)/12) = (2x/3) + 1

Please help Thanks! :confused: :confused:

Beth

Printable View

- Mar 15th 2006, 11:01 AMBethfor88Help please
I need to solve for ALL values of x:

(5(x-4)/6) + ((x+4)/12) = (2x/3) + 1

Please help Thanks! :confused: :confused:

Beth - Mar 15th 2006, 11:11 AMearbothQuote:

Originally Posted by**Bethfor88**

multiply your equation by 12 (it's the common denominator of all the fractions) and you'll get:

$\displaystyle \frac{5(x-4)\cdot 12}{6}+\frac{(x+4)\cdot 12}{12}=\frac{2x\cdot 12}{3}+1\cdot12$

simplify to:

10(x-4)+(x+4)=8x+12

3x=48

x=16

There are no other solutions.

Greetings

EB - Mar 15th 2006, 11:13 AMBethfor88
Thanks that helped :D